POLITICAL CONSENSUS ON CLIMATE CHANGE RESILIENCE IN CHITRAL: PROSPECTS AND CHALLENGES - Sabahat Rahim Baig (International Journal of Contemporary Issues in Social Sciences, 2024)
This research endeavors to address the critical issue of the absence of a unified political consensus on climate change in the Chitral region of Pakistan. Situated in a geographically vulnerable area characterized by mountainous terrain, Chitral faces escalating climate-related threats such as flooding, landslides, and glacial lake outburst floods (GLOFs). Despite these risks, coordinated political efforts to tackle climate challenges and build resilience remain lacking. This research seeks to unravel the underlying factors that have hindered the establishment of a shared consensus on climate change and propose strategies for its revival. Through a comprehensive methodology involving literature review, key informant interviews, focus group discussions, content analysis, and comparative analysis, the research aims to shed light on the intricate relationship between political dynamics and climate change concerns. The research will uncover the diverse interests, perspectives, and priorities of political actors and stakeholders, analyze discourses, and identify barriers to consensus. Drawing on successful consensus-building experiences from other regions, the research will propose policy options and communication strategies to foster collaboration and prioritize climate resilience and adaptation. The significance of this study lies in its potential to drive transformative change in the Chitral region's response to climate challenges. By bridging political divides and generating collective commitment, the research seeks to contribute to policy interventions that safeguard lives, livelihoods, and infrastructure. Moreover, the research's findings have broader implications for climate governance, inspiring collaborative action in regions facing similar challenges. Ultimately, this research envisions a future where Chitral's resilience to climate change is fortified through renewed political consensus, propelling sustainable development and improved well-being for its communities.